Exemplifying and numeration as ideological discursive devices in Al Arabiya and Al Jazeera’s Gulf crisis 2017 reporting - Jasim, Samir A.; Abdul Jabar, Mohd Azidan; Abdul Halim, Hazlina; Jalaluddin, Ilyana (Elite Scientific Publications, 2024)
This paper as part of its contribution to the world of knowledge seeks to extensively present a critical analysis of the online news reportage of one of the frosty Gulf crises in 2017 by two of the most popular agencies in the Arab world; Al Arabiya and Al Jazeera. News producers as well as news writers of these two news agencies employ various strategies towards propagating their ideologies to the world. The paper, therefore, examines the linguistic cues that these news agencies use in reporting the 2017 Gulf Crisis. The study adopts Jeffries’s Critical Stylistic Approach of (2010) through corpus approaches to analyse the news corpora of Al Arabiya and Aljazeera English. The study particularly, focused on the first month of the presumptive crisis. The use of mixed methods; quantitative and qualitative paradigms were upheld in the study to analyze the ideological consequences present in their discourses, focusing on the utilization of exemplifying and numeration strategies. The analysis highlighted how Al Arabiya has selectively listed and exemplified Qatar’s activities to promote an anti-Qatar ideological narrative, invoking guilt, and creating unity against Qatar. These strategies aimed to shape readers’ perceptions and create a negative image of Qatar by emphasizing allegations of support for terrorism and extremism. Al Jazeera on the other hand has used these strategies to question and discredit the allegations and emphasize the power dynamics in the region rather than genuine concerns about fighting terrorism. The strategies have portrayed the blockade as a political move disguised as a counterterrorism effort, with Qatar being portrayed as a victim of regional power games.